Effect of antiplatelet agents clopidogrel, aspirin, and cilostazol on circulating tissue factor procoagulant activity in patients with peripheral arterial disease - Rao, A. Koneti; Vaidyula, Vijender R.; Bagga, Shagun; Jalagadugula, Gauthami; Gaughan, John; Wilhite, Douglas B.; Comerota, Anthony J. (Thrombosis and Haemostasis, 2006)
Tissue factor (TF) is the physiological initiating mechanism for blood coagulation. Platelets play an important role in monocyte TF expression, thrombosis and inflammation. Aspirin, clopidogrel and cilostazol, which inhibit platelet responses by different mechanisms, are widely used in patients with arterial diseases. We tested the hypothesis that platelet-inhibiting agents inhibit the levels of circulatingTF procoagulant activity (TF-PCA) in patients with peripheral arterial disease (PAD).Twenty-six patients with lower extremity PAD, average age 65.9 ± 8.4 years (mean± SEM), were studied at baseline and following sequential twoweek treatment regimens with aspirin (325 mg daily), clopidogrel (75 mg daily) or a phosphodiesterase inhibitor cilostazol (100 mg twice daily) singly, and with each possible combination of these agents. Circulating TF-PCA in whole blood, and plasma factor VIIa, prothrombin fragment F1.2, thrombin-antithrombin complexes (TAT), and P-selectin were measured. Baseline TFPCA levels in the patients were elevated (131 ± 19 U/ml) compared to control subjects (23 ± 2, p<0.0001).TF-PCA levels declined following treatment with clopidogrel alone, and with combinations of clopidogrel with aspirin or cilostazol, with the lowest levels being with the triple-drug combination. Plasma P-selectin declined in all treatment groups. No changes were noted in plasma factorVIIa, F1.2 or TAT.In conclusion, treatment of PAD patients with antiplatelet agents decreases circulatingTF, a molecule with prothrombotic and proinflammatory effects. These findings suggest an unrecognized mechanism, beyond inhibiting aggregation responses, for the efficacy of antiplatelet drugs in patients with arterial diseases.
Keywords: Aspirin; clopidogrel; tissue factor; peripheral vascular disease; platelets